Evaluation of a rapid method for identifying Branhamella catarrhalis. Issue 4 (April 1988) - Richards, J
Abstract : The speed and precision of hydrolysis of tributyrin to butyric acid as a test to detect Branhamella catarrhalis were evaluated. The test proved consistently reliable in the identification of strains and correctly differentiated B catarrhalis from Neisseria sp. The combination of Gram stain, oxidase, and catalase tests to tributyrin hydrolysis provides a means of positive same day identification of B catarrhalis.